2017
DOI: 10.14738/abr.510.3693
|View full text |Cite
|
Sign up to set email alerts
|

Impact Of International Public Sector Accounting Standards Adoption On Accountability In Public Sector Financial Reporting In Nigeria

Abstract: This study examined the effect of adopting International Public Sector Accounting Standards (IPSAS) on accountability in public sector financial reporting in Nigeria, using the perceptions of accounting personnel (AP), academics (AA, and auditors (AU). A sample of 130 respondents was drawn from a population of 193 AU, AP, and AA within Benue State. The Chi-Square goodness of fit test, Kruskal Wallis H test, Mann-Whitney U test, and Cohen effect size were used in data analysis. The study found that IPSAS adopti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The Board launched the IPSAS as global standards for preparing and presenting public sector financial statements (Adamu and Ahmed, 2014). Thus, IPSAS comprises cash and accrual basis of accounting (Duenya et al, 2017). So, consolidated accounts of all public entities are required to be prepared by the central government of a country adopting IPSAS (Khan et al, 2014).…”
Section: Ipsasmentioning
confidence: 99%
See 1 more Smart Citation
“…The Board launched the IPSAS as global standards for preparing and presenting public sector financial statements (Adamu and Ahmed, 2014). Thus, IPSAS comprises cash and accrual basis of accounting (Duenya et al, 2017). So, consolidated accounts of all public entities are required to be prepared by the central government of a country adopting IPSAS (Khan et al, 2014).…”
Section: Ipsasmentioning
confidence: 99%
“…Another study was conducted by Duenya et al (2017) on the effect of adopting IPSAS on accountability in public sector financial reporting in Nigeria. Primary data were collected from a sample of 130 from a population of 193 accounting personnel (AP), academics (AA) and auditors (AU) within Benue State.…”
Section: Implementation Of Ipsas: An Overviewmentioning
confidence: 99%
“…Past studies have reported that developing countries are implementing them as a mere fashion, accompanied by non-preparedness of accountants and auditors [5,6,7,8]. In addition to that, most of them are adopting and implementing accrual-based IPSAS as a response to pressure from development partners [1,9,10,11,12,13]. This indicates that there are factors that influence the implementation of accrual-based IPSAS, in the Public Authorities, Local Government Authorities (LGAs) and Central Government [14,3].…”
Section: Introductionmentioning
confidence: 99%
“…According to Nweze (2013) These are accrual system and cash basis accounting. The embracing of International Public Sector Accounting Standards has some usefulness purposes such as demonstrate the correctness and reasonableness of transactions and their agreement with established rules; give evidence of accountability for the stewardship of government resources; make available vital information for good control and prudent management of government activities, contributing to the improvement of evaluation of financial performance as the financial statements will reflect all expenditures and incomes, providing evidence on whether revenue streams are suitable to meet short and long term liabilities; making comprehensive information relating to expenditure available which can help in knowing the cost implications of policies and enabling comparison with substitute policies; determining the future sustainability of programmes, liquidity position and comprehensive information on the financial position of government at the end of the financial year; and improving good governance (Okoye and Ani, 2004;Duenya, Upaa and Tsegba, 2017).…”
Section: Public Sector Accountingmentioning
confidence: 99%